Predicting thermoelectric performance of AlGaSbAs-based systems for thermo-photovoltaic cell applications - Merabet, Boualem; Maleque, Md. Abdul; Belhachi, Sofyane; Masood, A Ibnu; Hossain, Mohammad Sayeed; Algethami, Abdullah A; Ali, Hafiz T (IOP Publishing, 2025)
The development of high-performance thermoelectric (TE) materials is critical for advancing thermophotovoltaic (TPV)technologies. To evaluate TE properties of AlGaSbAs-based systems, highlighting their potential for efficient thermal energy conversion in TPV cell applications, this paper explores and selects a new material that predict TE performance of TPV system while ensuring environmental sustainability. The study further delves into material-specific performance with a case study on AlGaSbAs, including thermal conductivity, bandgap (Eg) engineering and figure of merit using a Python simulation tool to improve the TPV cells’ quantum efficiency and thermal stability. Using such a predictive computational framework, key TE parameters are quantified: figure of merit (ZT∼1.5–2.5), Seebeck coefficient(S: 150–300 μV/K), electrical conductivity (103 –104 S m−1 ), and thermal conductivity (κl of 0.91 W mK−1 at 1100 K). Suitable Eg of Al0.125Ga0.875Sb0.75As0.25 (0.554 eV) ensures alignment with mid-infrared photon energies, optimizing energy conversion in TPV systems operating at 500–1200 K. Innovations include alloy engineering to enhance phonon scattering, nanostructuring to minimize lattice thermal conductivity (κl ), and doping strategies to boost power factor. This study establishes AlGaSbAs as a scalable, thermally stable, and environmentally friendly material for next-generation TPV systems, providing a pathway for integrated TE and photovoltaic energy conversion solutions. The results showed that the thermal conductivity decreases with increasing temperature following a trend where it is inversely proportional to temperature which is beneficial as it suggests reduced heat loss at higher temperatures. S coefficient showed a linear increasing trend with the increasing of temperature demonstrating that the material becomes more effective at converting temperature differences into electrical voltage at higher temperatures. With controlling thermal parameters and selecting of the most suitable material, the efficiency of AlGaSbAs-based TPV cells can be significantly improved, making them more viable for high-temperature applications.